As representações dos professores de inglês do Ensino Médio sobre os PCN e a sua aplicabilidade - Macau, Liliane Mariano Ramos (2006)
This study aimed at identifying and interpreting the representa tions of a group of teachers of English upon the guidelines of the Parâmetros Curriculares Nacionais do Ensino Médio (PCN-EM) and their applicability, as well as upon the study plan and its objectives and contentens. The theoretical framework adopted for the development of this research was: social representations (Moscovici, 1984); tacit knowledge (Polanyi, 1967); reflection (Schön, 1984); theoretical knowledge (Demo, 1995); and the PCN-EM (2002). The methodological approach chosen was the case study (Stake, 1988), and the research context was a group of 12 High School English teachers. Taking into account the adopted methodological guideline, the identification and interpretation of the teachers´ representations were achieved through the analysis of the units of meaning that emerged from data (van Manen, 1990). The results of the analysis showed that the teachers perceive the PCN-EM guidelines as being valid, badly understood and topic for discussions. As for the study plan, in terms of its objectives and content, teachers perceived it as being a fundamental tool for organizing, orienting, measuring and controlling what needs to be done, and therefore they believe it must be re-elaborated in conjunction with other teachers, whenever necessary. Finally, the participants have the representation that the factors that allow PCN-EM applicability are the discussions and the clarification of these guidelines, during meetings with pedagogical coordinators, according to the teachers representations. The factors that still prevent its applicability are the excess number of students per class, the lack of teaching aids, the teachers´ isolation, and the lack of time and opportunities for discussing and clarifying the PCN-EM s contents. Data collected and analyzed in this research may be useful in future studies on foreign language teachers education, especially English teachers, from the perspective of the PCN-EM